A Modified Ice Water Path Retrieval Algorithm Applicable to the ATMS. Issue 1 (1st January 2019) - Xu, X.; Zou, X.
Abstract: The algorithm to retrieve the ice water path (IWP) from Microwave Humidity Sounder (MHS) measurements of two window channels at 89 and 157 GHz was already developed, and the IWP retrieval products have been made operationally available since NOAA-15. An adaptation of the same algorithm to the Advanced Technology Microwave Sounder (ATMS) is not straightforward due to differences of central frequencies and fields-of-view (FOVs) of the window channels between ATMS and MHS. In this study, ATMS and MHS orbit data from May 2016 to April 2017 are first collocated using the Simultaneous Nadir Overpass (SNO) method. Then two linear relationships between ATMS and MHS window channels are established using the SNO data: one between MHS channel 1 (89.0 GHz, 15-km nadir resolution) and ATMS channel 16 (88.2 GHz, 32-km nadir resolution), and the other between MHS channel 2 (157.0 GHz, 15-km nadir resolution) and ATMS channel 17 (165.5 GHz, 16-km nadir resolution). Since MHS IWPs are calculated differently when the scattering parameters are small ( Ω 89 <0.15 or Ω 157 <0.18) or large ( Ω 89 ≥ 0.15 and Ω 157 ≥ 0.18), the histogram of IWP is found to have an unrealistic local minimum around 0.4 kg m −2 . A modification is made to use the same algorithm as MHS when the scattering parameter at 89 GHz Ω 89 <0.08 or Ω 89 >0.19, and a linear interpolation within the interval of 0.08 ≤ Ω 89 ≤ 0.19 . The ATMS IWP is then derived using the modified algorithm by obtaining equivalent MHS brightness temperatures according to the regression relationships, while the MHS IWP is derived directly using the modified algorithm. Also, the ATMS results are collocated with MHS orbits for comparison purposes. The spatial distributions of ATMS- and MHS-derived IWPs are consistent. A quantitative analysis shows that the two results are approximately same with deviations smaller than about ± 0.02 kg m −2 .